Double blinded, placebo-controlled, randomised prospective intervention trial : to investigate the effectiveness of Bioslim in weight-loss and the influence of branding and advertising on the placebo response - Lee, Tzu-Ting (Stellenbosch : Stellenbosch University, 2012)
Thesis (MNutr)--Stellenbosch University, 2012.